Status Dan Hak Waris Anak Dari Orang Tua Yang Membatalkan Perkawinan Menurut Undang-Undang Perkawinan - Rifdah Khoirunnisaa Ramli; Barzah Latupono; Sabri Fataruba (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: The legal consequences of the annulment of a marriage begin after the ruling has a fixed and in force since the date of marriage was carried out according to chapter 28 of the marriage act. If a marriage is null and void, it is as if it never existed. However, the decision did not affect the status of children born from the marriage. However, in the case of the marriage annulled between the jesica iskandar and Ludwig Franz willibald, there were circumstances in which Ludwig was not responsible for their son, even barack Alexander, who looked after and paid for the child himself. This kind of research is normatitic juridical normative legal research, since it is done or aimed solely on written regulations. The data used are secondary data consisting of primary legal materials consisting of marriage laws, court rulings, relevant legal documents, and relevant legal literature on research topics. Studies have shown that in the case of annulment, the child born of the marriage remains legally recognized and valid. However, a child's birthright can be affected by a judicial decision that annuls the marriage. The marriage act provides guidelines on the protection and fulfillment of children's rights in this context. The study also identified some issues that arise regarding the status and rights of children born to parents who annul marriages. Among the issues found are the need for clarity in the appropriation of child custody, the sharing of common property, and the protection of the child's rights in the process of annulment of marriage. In addressing the issue, the study offers recommendations for improved legal regulations and increased public awareness of the importance of protecting the rights of children in the case of annulment of marriages. Additionally, work is required to increase accessibility and resolution rates of child status and birthright cases through an effective family judicial system.